Pengaruh Self-Efficacy Terhadap Hasil Belajar Matematika Pada Pembelajaran Tatap Muka Terbatas - Ismawati, Yesi; Latif, Burhanuddin (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
The achievement of learning outcomes is usually influenced in students, one of which is self-efficacy. This study aims to determine the effect of self-efficacy on mathematics learning outcomes for students at 9th grade of MTsN 5 Sleman in limited face-to-face learning. This study uses a quantitative approach ande the type is survey research. The data collection instrument used a self-efficacy questionnaire and mathematics learning outcomes were obtained through a daily assessment test of geometric transformation material. The analytical technique used descriptive statistical analysis and inferential statistical analysis, namely simple linear regression. The results showed that: (1) the contribution of self-efficacy influence of independent variables on the dependent variable mathematics learning outcomes by 2.3% and the remaining 97.7% is influenced by other variables not examined, (2) the analysis results showed that the value of thitung = -1.135 <t???????????????????? = 2,005 with significant value = 0.261 > α = 0.05, so there is no influences of self-efficacy on learning outcomes math class IX students MTsN 5 Sleman-face learning is limited, which means influenced by other factors which is not the focus of this study. Keywords: mathematics learning outcomes, limited face-to-face learning, self-efficacy